Learning for Children with Special Needs at SLB Negeri Magelang - Restu Retnaning Gusti; Adelia Dwi Risnawati; Sekar Hapsari Avio Imani; Ahmad Dani Yuliyanto; Aditia Eska Wardana (Prosiding University Research Colloquium, 2022)
Children with Special Needs are children who have their own uniqueness in their types and characteristics, which distinguish them from normal children in general. The purpose of this study was to find out how the learning process for children with special needs in SLB N Magelang City. In addition, to determine the supporting and inhibiting factors in learning for children with special needs. This research is a qualitative type of research with data collection instruments through observation, in-depth interviews and documentation. The results showed that the classification of children with special needs in SLB Negeri Magelang City there are 5 types, namely blind, deaf, mentally retarded, quadriplegic and speech impaired. In improving students' abilities during learning, teachers at SLB N Magelang City first look at the needs of the child according to the child's own ability. Factors supporting learning for children with special needs are adequate facilities and infrastructure, teachers are always patient with students and painstaking in teaching children. Meanwhile, the obstacle to learning for children with special needs is in providing education to students, the main factor is the environment, because many children have very affordable distances between home and school.